Bridging disparate symptoms of schizophrenia: a triple network dysfunction theory - Nekovarova, Tereza; Fajnerova, Iveta; Horacek, Jiri; Spaniel, Filip (Frontiers in Behavioral Neuroscience, 2014)
Schizophrenia is a complex neuropsychiatric disorder with variable symptomatology, traditionally divided into positive and negative symptoms, and cognitive deficits. Yet, the etiology of this disorder has yet to be fully understood. Recent findings suggest that alteration of the basic sense of self-awareness may be an essential distortion of schizophrenia spectrum disorders. In addition, extensive research of social and mentalizing abilities has stressed the role of distortion of social skills in schizophrenia. This article aims to propose and support a concept of triple brain network model of the dysfunctional switching between default mode and central executive network related to the aberrant activity of salience network. This model could represent a unitary mechanism of a wide array of symptom domains present in schizophrenia including the deficit of SELF (self-awareness and self-representation) and theory of mind (ToM) dysfunctions along with the traditional positive, negative and cognitive domains. We review previous studies which document the dysfunctions of SELF and ToM in schizophrenia together with neuroimaging data elucidating the triple brain network model as a common neuronal substrate of this dysfunction.